LINE IDENTIFICATION IR SPECTRA OF MOLECULES OF FORMIC ACID FOR USE IN ENVIRONMENTAL MONITORING - Alanko, S.; HornemanV.-М.; Баскакова, Л. В.; Баскаков, О. І. (Man and Environment. Issues of Neoecology)
We investigate the poorly understood fundamental infrared band ν2 isotopic variations of formic acid molecules DCOOH. The identification of spectral lines is to determine the rotational quantum number of levels, which correspond to transitions between those lines. To solve the problem the method of combination differences applied to a series of similar lines. Done measuring wave numbers absorption lines of basic IR bands ν2 molecules DCOOH order of accuracy 0,0003 cm-1. The method of combinational differences identified more than 2000 transitions mainly type b.